Pengembangan Sistem Monitoring Smarthome Secara Pervasif Dengan Nodemcu Dan Smartphone - Reva Ade Wardana; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Smarthome or what we usually call smart home is a house or building equipped with high technology that allows various systems and devices at home to communicate with each other. In Indonesia alone, smarthome technology is still in the introductory and familiarization stage to the community, the challenge of the smarthome concept is entering the realm of the smallest and most intimate community, namely the family, There are so many ways to implement a smarthome in daily life, such as the use of sensors to detect changes in the physical or chemical environment, turning on or turning off devices using smartphones, or simply monitoring the condition of the house remotely. In addition, the concept of IoT (Internet of Things) is one part that cannot be separated in the development of this technology, this concept can greatly help humans to streamline their time and help carry out activities with this problem. this system parameters are used to monitor. There are four sensors to monitor the state of the house, this system works automatically without user intervention. Then the Pervasive Computing method will communicate between Nodes. In this study the estimated time used for communication between nodes is approximately 4578- 5097ms.